Planejamento emergente em serviços de saúde: a experiência bem-sucedida do gerenciamento estratégico em Pirapora - Juliana Gomes Cabral de Almeida (2011)
Due to the necessity of strategic management implementation at municipal level, a room of healthcare management, known as Situation Room (SASI) was established in Pirapora, MG, becoming a pioneer and successful experiment in this kind of management. SaSi members, managers and heath professionals draw up strategies from mapping and analysis of healthcare data, in particular, from Family Heath Program (PSF), which cove up more than 83% of the population. The objective of this research is to demonstrate through a case study - examining Prevention of Cervical Cancer - how to combine strategic planning, planning emergent (non-conscious and prior planning) and strategic thinking (creativity), considering the contribution of different hierarchical levels, in order to explain how it was possible to achieve goals targeted by the State Heath Secretariat (SES). The hypothesis that the success of SaSi can be explained by the "strong" combination of strategic thinking of their managers and practical experience of operating units professionals was confirmed by this qualitative research, specifically ethnography. Actions taken, sometimes by planners or by performers and sometimes by both, made all the difference. Starting at a lower level of complexity, evolving to the greatest, we can say that the actions were: 1. Disclosure of information and knowledge on the exam and cancer, such as information of dates, times, sample collection in basic heath units (BHU) by trained professionals; clarification of examination importance, the relationship between exam and hysterectomy (surgery partial or total removal of the uterus) and virginity; fighting false beliefs about the collection procedures, the relationship between cancer and death; 2. Institutional and organizational change: alternative schedules, frequency and days of collection, gender of nurse, stipulation deadline for sending samples to the lab, suitability and reallocation of material resources, personnel and infrastructure for collection, intensive workdays. 3. Support for actions on the situation: monitoring and assessment of actions convincing face to face. Some factors that contributed to achieving the goal were: 1) the contribution of prior experience in the team's SaSi PSF, the local knowledge arid practices, and intangible assets of factual information for the recognition and appreciation of actions developed by professionals, from satisfactory results, allowing it to spread good practice with other UBS; 2) the possibility of adjustments the (re) adjusting the strategic plan suggested by SaSi locally and to the creation of a new action by the executors, considering the particularities that surround them, when at one moment, it is up to each professional, the production of argumentative persuasion face-to-face, when SaSi structure have no effect for the process. Some characteristics of a "Community of Practice" influenced the density of relationships between professionals, creating a mutual commitment, an individual and collective responsibility in search of better performance add results, commonly mediated by a shared instrument, resulting from the social production of SaSi and PSF professionals. Finally, it will alert to the risks arising from the management by results of the analysis of quantitative data or just from not knowing what to do with numbers, culminating on a penalty, dissatisfaction and loss of sense of work. Know how to analyze qualitative data between the lines and enable the (re)negotiation of goals are also some of the steps needed for success.